Efektivitas Program Tadabbur Al-Qur’an dalam Peningkatan Akhlak Siswa di MI Al Fithrah Surabaya - Moh. Taufiq (Departement of Mathematics Education, 2020)
Tadabbur Al-Qur'an is one of the teaching programs in the junior high school environment which aims to foster and develop polite and harmonious relationships between students and Allah, between students and each other, and between students and their environment. Many factors influence the success of a person's life, one of which is having good morals such as wisdom, generosity, renewal, steadfastness, chivalry, justice and others. The Al-Qur'an Tadabbur Program at MI Al Fithrah Surabaya is a form of madrasah program in an effort to shape student morality, the authors submit this evidence after the authors conducted research at the madrasah. The type of research used in this research is quantitative